Strategy as Practice: A study of the practices of strategic action in the SMEs store cluster - Luiz Marietto, Marcio; Sanches, Cida (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This study through ethnographic procedures and Strategy-as-Practice assumptions, grounded specifically the ActivityBased View theory, show how the individuals (owners, entrepreneurs, managers, salespeople and other social actors) in the small store cluster interact with the internal and external environmen t formulate, influence and execute strategies through and between organizations to ensure the dynamic durability of the small stores and the cluster. The analytic results point to the dynamic adaptation of social actors ability of small stores to share mea nings in the daily achievement of strategizing embedded in the institutional dynamic context of the rituals, ceremonies and symbolism of the institution of marriage.